Gender Mainstreaming in Rural Road Construction & Usage in Ethiopia: Impact & Implications. Issue 3 (27th June 2019) - Abhishek, Abraham; Borgia, Cecilia; Manjur, Kebede; van Steenbergen, Frank; Vera, Letty Fajardo
Abstract : This paper investigated the engagement of men, women spouses (WS) and women heads of household (WHH) in planning and construction of rural roads in two Ethiopian districts of Tigray and Amhara regions, and differential impacts of rural roads on mobility and transport on men, WS and WHH. Fieldwork established that there is a strong demand among women for road use and for employment opportunities in road construction; women compared to men exhibit specific priorities with respect to rural road development, such as access to ambulance services, flat, wide, and levelled roads, and improved access to means of transport. Although women's concerns have been slowly but steadily pushed up the planning agenda, there are gaps between gender provision in rural road development and implementation, Benefits of roads for women can be enhanced by targeting gender mainstreaming provisions to take into account the specific travel and transport needs of WS and WHH.